Impact of an oral gonadotropin‐releasing hormone antagonist on severe ovarian hyperstimulation syndrome in a patient with breast cancer who received a sustained‐release gonadotropin‐releasing hormone agonist: A case report. Issue 12 (12th October 2021) - Hanada, Tetsuro; Kimura, Fuminori; Kitazawa, Jun; Morimune, Aina; Murakami, Takashi
Abstract: Postoperative hormone therapy for hormone‐sensitive patients with breast cancer is important to prevent a recurrence. As hormone therapy does not induce infertility in patients, fertility‐preserving therapy is not provided during treatment. Here, however, we performed controlled ovarian stimulation and embryo freezing for fertility preservation under the influence of a sustained‐release gonadotropin‐releasing hormone agonist in a patient with breast cancer whose postoperative treatment plan was changed from hormone therapy to chemotherapy. After oocyte retrieval, the patient developed treatment‐resistant severe symptomatic ovarian hyperstimulation syndrome. Following treatment with oral gonadotropin‐releasing hormone antagonist, her symptoms immediately improved, and she could receive chemotherapy on schedule.